2017
DOI: 10.1073/pnas.1713826115
|View full text |Cite
|
Sign up to set email alerts
|

Localizing softness and stress along loops in 3D topological metamaterials

Abstract: Topological states can be used to control the mechanical properties of a material along an edge or around a localized defect. The rigidity of elastic networks is characterized by a topological invariant called the polarization; materials with a well-defined uniform polarization display a dramatic range of edge softness depending on the orientation of the polarization relative to the terminating surface. However, in all 3D mechanical metamaterials proposed to date, the topological modes are mixed with bulk soft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…These works suggest that tunable amorphous materials have the flexibility required to produce elaborate designs, as recently demonstrated by mimicking the cyclical conformational motion of protein motors [Flechsig and Togashi 2018]. These promising approaches to metamaterial design are discussed elsewhere, for example in [Baardink et al 2018;Kim et al 2018;Rocklin 2017;].…”
Section: Biology As a Challenge To Theoristsmentioning
confidence: 94%
“…These works suggest that tunable amorphous materials have the flexibility required to produce elaborate designs, as recently demonstrated by mimicking the cyclical conformational motion of protein motors [Flechsig and Togashi 2018]. These promising approaches to metamaterial design are discussed elsewhere, for example in [Baardink et al 2018;Kim et al 2018;Rocklin 2017;].…”
Section: Biology As a Challenge To Theoristsmentioning
confidence: 94%
“…Topology plays an important role in these elastic systems, giving rise to topologically protected phonon-edge modes at zero frequency (or floppy modes). Maxwell lattices appear in nature in systems such as fiber networks [8] and jammed packings [9], as well as in artificial metamaterials as mass-spring systems (including other mechanical devices), both insulators and Weyl semimetals [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, higherorder topological insulators rely on the existence of crystal symmetries that typically limit the robustness of the edge modes. Moreover, it has been shown that protected modes can also be localized to points or lines of dimensionality lower than (d -1) in ordinary topological insu lators that have mater ial defects [11][12][13][14] . Finally, one can speculate about such systems beyond third order -in other words, beyond the octupole moment.…”
Section: From Nature 14 March 1918mentioning
confidence: 99%